WAYANG IN ISLAMIC PHILOSOPHY - yuyun yunita (Ri'ayah: Jurnal Sosial dan Keagamaan, 2020)
Wayang kulit is named after Javanese wayang which means shadow or taken meaning that wayang is a depiction of life or a reflection of the various human traits found in various souls of the human conscience itself. The universe itself is divided into various types into two basic traits such as wrath and kindness. The history of the story of Dewa Ruci as one of the puppet plays is a cousin of the many ways and rich in philosophical values ​​of religious diversity that is so profound. The history of this story depicts a man or man who has a lot of strong will to find the best ways that can be considered to bring people to happiness. In the search for happiness, it is not easy to do because it will be many and there are obstacles or prevention that may be faced by many. This is where the aesthetic value or beauty is packaged and wrapped up in the history of the gods of Ruci and becomes the first and foremost doctrine of the conception of the divine, humanity, and respect of the human beings with the creator or than. the story of the goddess Ruci outlines or philosophically symbolizes how human beings must go through and make an inner journey to find their true identity or look for paraning dumadi the origin and purpose of life in human beings or tackle the human gusti, the conception of God and how humans lead to God, the wayang kulit is very much, the art of wayang puppets cannot be retracted from history, which the bags are retold through wayang.